Robust Control Design for an Active Magnetic Bearing System Using Advanced Adaptive SMC Technique - Syed Muhammad Amrr (IEEE, 2021)
Fast rotating machines require special attention to ensure accurate rotor placement within the air gap. For this reason, the active magnetic bearings (AMB) system is used to levitate the rotor in the air gap using an electromagnetic feedback control force. The contact-less support AMB system improves the rotor dynamic performance and helps in the success of machine operations. However, the control design for the five degrees-of-freedom (DOF) AMB system is intricate because of its complex nonlinear dynamics. Moreover, these systems are often subjected to model uncertainties, harmonic disturbances, and sensor noises. Therefore, this paper proposes a robust control strategy using an adaptive second-order non-singular fast terminal sliding mode control (SMC) design. The proposed control law employs the higher-order SMC scheme to alleviate the chattering problem from the discontinuous SMC input, which would otherwise restrict its practical applicability. Further, a non-singular fast terminal sliding surface is selected to achieve a faster system response. The adaptive law estimates the switching gain to relax the upper bound assumption of disturbance. The theoretical stability analysis of the proposed methodology proves the finite-time convergence of system states to a small residual bound in the neighborhood of zero. The numerical analysis with a comparative study is also carried out to illustrate the efficacy of the proposed strategy.